Tricky nelly's birthday treat - Doherty, Berlie; Ross, Tony (Walker London, 2003)
Tricky Nelly Nickleby and Billy the Bamboozler are always playing tricks on each other. So when Nelly asks for a pretty feather hat for her birthday, Billy comes up with a crafty plan to give her what she wants and more. But Nelly has plans of her own to make him look like a silly Billy! Suggested level: primary